LOAD FREQUENCY CONTROL FOR AN ISOLATED HYBRID POWER SYSTEM WITH HYBRID CONTROL TECHNIQUE AND COMPARATIVE ANALYSIS WITH DIFFERENT CONTROL TECHNIQUES - Kirn Kumar, N.; Indra Gandhi, V. (Malaysian Journal of Computer Science, 2020)
This paper presents a hybrid isolated power system modeling and Load Frequency Controller (LFC) for different penetration levels of wind power generation. The system considered here consists of a conventional diesel generator, wind generator and energy storage system for a LFC. The purpose of the considered system is to suppress the frequency deviations (balancing the real power generation and demand). An inertia control is used to obtain the best possible gain of the wind system and Fuzzy Logic Control (FLC) is used to control the frequency of the hybrid system. The results are compared with different control techniques. The dynamic performance of the system is studied at different cases by changing the wind penetration level and also by increasing the load disturbances.